HUMAN DEVELOPMENT INDEX OF NIGERIA AND INDIA: AN OVERVIEW OBSERVATION - Yaruingam, Prof. A. S.; Gupta, Ms. Jyoti (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2023)
A long and healthy life, access to knowledge, and a reasonable standard of living are the three fundamental dimensions of human development that the HDI measures in summary form over time. The life expectancy at birth is used to evaluate the health dimension, and the mean number of years spent in school for adults 25 years and older and the anticipated number of years spent in school for young children are used to evaluate the education dimension. Gross national income per person is used to measure the standard of living dimension. The HDI uses the logarithm of income to reflect how income becomes less significant as GNI rises. The three HDI dimension indices' scores are then combined using geometric mean to create a composite index.